2011
DOI: 10.1177/0884533611419859
|View full text |Cite
|
Sign up to set email alerts
|

Nutraceutical Supplements for Weight Loss

Abstract: Obesity is a global public health issue. Although the etiology of this global epidemic is multifactorial, most sufferers would be delighted to find a relatively effortless way to lose weight. Herbal "weight loss pills" can fit the bill. The authors systematically review the scientific evidence concerning various weight loss agents that are available over the counter or in food stores. The review provides a starting point to make informed choices among nutraceutical agents promoted for weight loss, as well as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 174 publications
(348 reference statements)
1
42
0
Order By: Relevance
“…A recent systematic review of the current literature by the Johns Hopkins’ Weight Management Center concluded that nonprescription dietary supplements as an adjunct to weight loss currently cannot be strongly recommended. (Poddar, Kolge,2011) Furthermore, these medications have not been adequately assessed in women with PCOS.…”
Section: Obesitymentioning
confidence: 99%
“…A recent systematic review of the current literature by the Johns Hopkins’ Weight Management Center concluded that nonprescription dietary supplements as an adjunct to weight loss currently cannot be strongly recommended. (Poddar, Kolge,2011) Furthermore, these medications have not been adequately assessed in women with PCOS.…”
Section: Obesitymentioning
confidence: 99%
“…The growing obesity prevalence may reflect the limited potential role of public health initiatives and current pharmacological treatments for contending obesity-related cardiometabolic disorders although this issue remains a matter of debate. Therefore, there is an urgent need to discover not only new powerful drugs, but also functional foods, which may synergistically help curb the epidemic of obesity-related metabolic diseases [2, 3]. Currently, various research groups advocate the use of milk-derived proteins, including Lf, as preventive and curative tools for alleviation of complex metabolic diseases [4, 5].…”
Section: Introductionmentioning
confidence: 99%
“…We captured all pages available from each program’s website between June 6 and June 11, 2014. We developed a coding scheme based upon 2013 AHA/ACC/TOS weight management guidelines (5) and prior reviews on efficacy of prescription medications and supplements for weight loss (15-16) to identify relevant content (Supporting Information S1). We considered supplements to include dietary supplements, nutraceuticals, or other products that are not approved by the Food and Drug Administration (FDA) in the treatment of obesity (e.g., vitamins, minerals, herbal, botanicals, amino acids, enzymes, hormones, etc).…”
Section: Methodsmentioning
confidence: 99%